Effects of the different types of materials used in passive vibration control systems for structures - Amamra Houria; Ben mekki Othmen; Limam Oualid (University Of Eloued جامعة الوادي, 2020)
The construction of structures (buildings, bridges, ... etc) is more and more complicated, it is for this reason, their design requires the satisfaction of an increasingly large number of constraints (type of materials, measurement security, control systems, ... etc).
Intervention
Keywords: control systems for structures; passive vibration control systems; materials used in passive vibration control systems; different types of materials used in passive vibration control